2003
DOI: 10.1073/pnas.0837153100
|View full text |Cite
|
Sign up to set email alerts
|

An obligate pollination mutualism and reciprocal diversification in the tree genus Glochidion (Euphorbiaceae)

Abstract: Highly coevolved pollination mutualism accompanied by reciprocal diversification has been known in only two plant genera, Ficus (Moraceae) and Yucca (Agavaceae), which are pollinated exclusively by obligate seed-parasitic wasps and moths, respectively. An additional, highly diversified, species-specific pollination mutualism between a monoecious tree genus, Glochidion (Euphorbiaceae), and a moth genus, Epicephala (Gracillariidae), is presented here. At night, the small female moth actively deposits pollen on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
227
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 168 publications
(235 citation statements)
references
References 15 publications
6
227
0
2
Order By: Relevance
“…It is likely, though, that more plants are pollinated by floral parasites than is currently known. For example, only within the past decade has pollination by insects during oviposition been discovered in the Phyllanthaceae in the tropical Pacific, involving possibly hundreds of plant species, and discovery of similar pollination mutualisms within this and other plant families continues (6,11,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely, though, that more plants are pollinated by floral parasites than is currently known. For example, only within the past decade has pollination by insects during oviposition been discovered in the Phyllanthaceae in the tropical Pacific, involving possibly hundreds of plant species, and discovery of similar pollination mutualisms within this and other plant families continues (6,11,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an obligate pollination mutualism between Glochidion trees (Phyllantaceae) and Epicephala moths (Gracillariidae) was recently described (Kato et al 2003). Several different methods for investigating the level of cocladogenesis between phylogenies indicated that there is a greater degree of correlation between the Glochidion and Epicephala phylogenetic trees than expected in a random association .…”
Section: Co-divergence In the Fig-wasp Symbiosis N Rønsted And Othermentioning
confidence: 99%
“…The tribe Phyllantheae (Phyllanthaceae) contains around 1200 species of monoecious or dioecious herbs/shrubs/ trees and nearly half of the species are pollinated only by female moths of the genus Epicephala (Gracillariidae) [10,11]. At night, Epicephala females visit male flowers and actively collect pollen grains using their modified proboscises (figure 1a).…”
Section: Introductionmentioning
confidence: 99%